Enhancing Learning through Deep Learning: Does It Foster Elementary Students’ Conceptual Understanding and Motivation in Mathematics? - Gianto Gianto; Wiryanto Wiryanto; Neni Mariana; Ulumul Umah (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2026)
Deep learning is an instructional approach with valuable potential for Indonesian education and has increasingly been integrated into classroom practices. However, empirical evidence regarding its effectiveness in fostering elementary students’ conceptual understanding and motivation in learning mathematics remains underexplored. This study utilized a quantitative quasi-experimental design to investigate the short-term effects of integrating a deep learning approach on their conceptual understanding and learning motivation in mathematics, especially in fraction topics. The participants were 60 third graders from two public elementary schools in Sepaku, East Kalimantan, Indonesia. This study employed convenience sampling strategy with one class selected as an experimental group and another assigned to a control group. Data were collected through a conceptual understanding test and a learning motivation questionnaire. The results revealed statistically significant differences between the two groups. The findings conclude that the implementation of deep learning approach contributes to students’ conceptual understanding and motivation in learning mathematics.